Pengaruh Economic Performance, Environmental Performance dan Good Corporate Governance Terhadap Nilai Perusahaan (Tobins’Q) - Utari, Indriana Tri; Khomsiyah, Khomsiyah (Owner : Riset dan Jurnal Akuntansi, 2024)
This research examines the company value that occurs in manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period. This study aims to prove that economic performance, environmental performance and good corporate governance affect the success of company value. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period, totaling 26 companies. The sample selection technique in this study was carried out by non-probability sampling. The analysis used descriptive statistical analysis and panel data regression analysis. The results of this study are economic performance has a significant effect on firm value, environmental performance has a significant effect on firm value and good corporate governance has a significant effect on firm value.